Konservasi Kampung Pecinan Semarang sebagai Media Integrasi yang Berdemensi Multikulturalism - Suzanna Ratih Sari; Eko Punto Hendro (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
This research aims to preserve the historic Chinatown of Semarang with the concept of preserving cultural heritage areas as mandated by Law No. 11/2010 on Cultural Heritage. Of course this effort is also a form of collective memory maintenance, because this village is very historical. The research method was carried out by observation, interviews and conservation planning. In the effort of preserving or conserving the cultural heritage areas, the concept of spatial planning with multiculturalism dimensions is also developed, meant that spatial planning is pursued in conjunction with cultural acculturation activities to reduce stereotypical social problems that still exist today.